Incidence and predictors of vascular events following end‐stage kidney disease in childhood. Issue 9 (10th May 2021) - Le Page, Amelia K.; Kennedy, Sean E.; Durkan, Anne; Chaturvedi, Swasti; Walker, Amanda; Sypek, Matthew P.
Abstract: Aim: Cardiovascular death is a leading cause of mortality in paediatric end‐stage kidney disease (ESKD). There is however little known about the clinically relevant vascular disease in this population. We aimed to describe the incidence of new onset vascular disease and vascular death in Australian children receiving renal replacement therapy (RRT). We also aimed to identify demographic or childhood risk factors for these endpoints, and whether vascular disease predicts mortality. Methods: Data on Australian patients who commenced RRT at <18 years of age from 1991 to 2017 were extracted from the Australian and New Zealand Dialysis and Transplant Registry (ANZDATA). Multivariable competing risks regression was used to identify factors associated with vascular events. Results: A cohort of 1268 patients were followed up for a median of 10.31 years. Vascular disease was reported in 5.4%, and vascular death in 4.1%. The cumulative incidence of any vascular event, that is, disease or death, at 10 and 20 years was 5.5% and 12.8%, respectively. Childhood vascular events were associated with non‐Caucasian, non‐Indigenous ethnicity, and for the 804 patients followed up after 18 years of age, vascular events were associated with lack of childhood transplantation, longer childhood dialysis duration and Indigenous ethnicity. Vascular disease was only reported for 25.49% of patients who had a vascular death, and although a significant risk factor for mortality, it had limited ability to predict mortality. Conclusion: Cumulative incidence of vascular events is significant after commencing RRT during childhood and is associated with ethnicity, longer childhood dialysis duration and lack of childhood transplantation. SUMMARY AT A GLANCE: During a median follow‐up of 10.3 years among children on dialysis, 5.44% had vascular disease and 4.02% died of vascular disease. Risk factors related to adverse vascular outcome include Indigenous ethnicity, longer dialysis duration, and lack of transplantation. This study highlights the importance of surveillance and management of vascular disease in children with ESKD, particularly for those in transition from childhood into adulthood.